2016
DOI: 10.2139/ssrn.2710547
|View full text |Cite
|
Sign up to set email alerts
|

Does Improving Public Transport Decrease Car Ownership? Evidence from the Copenhagen Metropolitan Area

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Any Denmark-wide changes would be addressed directly with our time controls, so any concern would have to be a region-specific change that is correlated with work distance. The only meaningful change we uncovered was the addition of a line to the Copenhagen metro between 2002 and 2007 (Mulalic, Pilegaard, and Rouwendal, 2015). This would not be captured in our variable for public transport access.…”
Section: Identificationmentioning
confidence: 94%
See 1 more Smart Citation
“…Any Denmark-wide changes would be addressed directly with our time controls, so any concern would have to be a region-specific change that is correlated with work distance. The only meaningful change we uncovered was the addition of a line to the Copenhagen metro between 2002 and 2007 (Mulalic, Pilegaard, and Rouwendal, 2015). This would not be captured in our variable for public transport access.…”
Section: Identificationmentioning
confidence: 94%
“…To address any possible endogeneity concern relating to our variable for public transport access, we also examine a specification where we instrument for public transport access with municipality-level population data from 1916, which is the earliest year complete municipality-level population data are available. 25 This approach follows Durantan and Turner (2011), Mulalic, Pilegaard, and Rouwendal (2015), and other recent papers using historical data that determine the location of rail and road lines, but otherwise should not influence outcomes today.…”
Section: Identificationmentioning
confidence: 99%
“…The authors accounted for the results by referring to the specific conditions of the urban areas under study. According to the study of Mulalic, Pilegaard, and Rouwendal [6] the extension of the metro system in Copenhagen led to a slight decrease in car ownership. At the same time, the city centre experienced a substantial increase in residents.…”
Section: Factors Influencing Transport-ownership Decisionsmentioning
confidence: 99%
“…While studies have shown that public transport supply has an impact on car ownership, it is typically low. All things kept equal, the large public transport investment such as a major extension of the underground network might decrease car ownership by 1% to 3% (Mulalic, Pilegaard, and Rouwendal, 2015). A plausible explanation is that public transport services do not offer the same level of flexibility than personal transportation because of uneven coverage in space and time, so owning a car is still necessary for occasional trips.…”
Section: A Tentative Outlookmentioning
confidence: 99%